Preliminary Exploration of the Cause of Liver Disorders During Early Stages in COVID-19 Patients - Gao, Yuan; Li, Qi; Shi, Hongbo; Feng, Yingmei; Zhang, Tong; Chen, Yu; Liang, Lianchun; Chen, Dexi; Wu, Hao; Jin, Ronghua; Huang, Xiaojie (Frontiers in Medicine, 2020)
Background Abnormal liver function is a common indication in coronavirus disease 2019 (COVID-19) patients. Two proposed mechanisms are liver injury mediated by angiotensin-converting enzyme 2 (ACE2) and the involvement of systemic immune response. We investigated the role played by these to determine the cause of liver abnormality in the early stages of COVID-19. Methods A cross-sectional study was conducted among confirmed cases of COVID-19 at Beijing Youan Hospital from January 21, 2020, to February 24, 2020. We compared clinical characteristics, viremia status, and cytokine profile on admission between patients with and without liver disorder. Results Of the 44 COVID-19 patients analyzed, there were no differences in the clinical symptoms and signs, disease severity, or computed tomography (CT) image features between the two groups. Lymphopenia was more common in the liver disorder group. Further, C-reactive protein levels were much higher in the hepatic disorder group, with significantly higher concentrations of IL-6, IL-10, and M-CSF. Viremia was detected in only 7% of patients. Conclusions Due to the infrequency of viremia, ACE2-mediated viral hepatitis does not seem to account for commonly observed liver disorder in COVID-19 patients. By contrast, dysregulated immune response may be a crucial pathogenic factor for liver disorder in the early stages of COVID-19.